Toxicological studies of a metabolite of Streptomyces species on Brine shrimp and Mice - Sathi, Zakia Sultana; Barman, Ranjan Kumar; Islam, M Anwarul; Rahman, Md Mokhlesur; Habib, Md Anwar (TAJ: Journal of Teachers Association, 2010)
The cytotoxic activity of the crude chloroform extract of Streptomyces species and a pure compound, 4-hydroxy nitrobenzene (ZS-3) isolated from chloroform extract was determined by brine shrimp lethality bioassay. The LD50 values of chloroform extract and compound (ZS-3) and ampicillin trihydrate were found to be 5.6, 6.6 and 5.0 μg ml-1, respectively. The acute toxicity of the compound (ZS-3) was also performed on Swiss albino mice. The median acute toxicity value (LD50) of ZS-3 was found to be 62 mg kg-1. Thus the isolated compound ZS-3 seems to be safe for therapeutic use. TAJ 2010; 23(1): 6-9